Multistage signal-interactive nanoparticles improve tumor targeting through efficient nanoparticle-cell communications - Zhang Feng; Zhang Yiran; Kong Li; Luo Huanhuan; Zhang Yuezhou; Mäkilä Ermei; Salonen Jarno; Hirvonen Jouni T.; Zhu Yueqi; Cheng Yingsheng; Deng Lianfu; Zhang Hongbo; et al. (Cell Press, 2022)
Communication between biological components is critical for homeostasis maintenance among the convergence of complicated bio-signals. For therapeutic nanoparticles (NPs), the general lack of effective communication mechanisms with the external cellular environment causes loss of homeostasis, resulting in deprived autonomy, severe macrophage-mediated clearance, and limited tumor accumulation. Here, we develop a multistage signal-interactive system on porous silicon particles through integrating the Self-peptide and Tyr-Ile-Gly-Ser-Arg (YIGSR) peptide into a hierarchical chimeric signaling interface with “don’t eat me” and “eat me” signals. This biochemical transceiver can act as both the signal receiver for amantadine to achieve NP transformation and signal conversion as well as the signal source to present different signals sequentially by reversible self-mimicking. Compared with the non-interactive controls, these signal-interactive NPs loaded with AS1411 and tanespimycin (17-AAG) as anticancer drugs improve tumor targeting 2.8-fold and tumor suppression 6.5-fold and showed only 51% accumulation in the liver with restricted hepatic injury.